Effect of Team Achievement Division Strategy on Academic Achievement of Guidance and Counselling Students in Anambra State, Nigeria - UBA, Mercy BenedetteIfeoma (Ilorin Journal of Education, 2024)
This study examines the effects of implementing the Students’ Team Achievement Division (STAD) cooperative learning strategy on academic achievement in guidance and counseling among tertiary education students in Anambra State, Nigeria. A quasi-experimental pretest-posttest control group design was used to compare the STAD strategy to conventional expository teaching methods. The sample consisted of 67 second-year students (14 male, 53 female) enrolled in the guidance and counseling program at Nnamdi Azikwe University. Students were non-randomly assigned to either the experimental group (n = 34; 7 male, 27 female) that received instruction using STAD or the control group (n = 33; 7 male, 26 female) taught via traditional lecture. Both groups completed a 40-item guidance and counseling achievement pretest. For six weeks, the experimental group utilized STAD during daily lessons while the control group received conventional lecture. Following the intervention period, both groups completed the identical posttest. Independent samples t-tests revealed no pretest score differences but significant posttest score increases for the experimental group compared to the control, indicating STAD positively impacted academic achievement. These findings suggest incorporating STAD cooperative learning into guidance and counseling instruction may enhance student performance outcomes by promoting collaborative learning and individual accountability. Further research is needed to replicate these results across different student populations, cultural contexts, and higher education settings.